Research on Improving the Performance of Air- source Heat Pump - Zhen Bing; Liu Zonghua; Wang Qixiao; Li Xiaoyan; Wang Ying; Ji Amin (Zhileng xuebao)
The problems for heat pumps operating at low ambient temperatures were analyzed.A by-pass capillary tube was added on the discharge pipe behind the four-way valve and a tube was added in an accumulator in a heat pump system to solve the problem.The minimum heat transfer area of the tube for subcooling and the optimal length range of the by-pass capillary tube were determined.The experiment results show that heat output of the improved heat pump increased greatly at low ambient temperatures.